2001
DOI: 10.1080/07391102.2001.10506752
|View full text |Cite
|
Sign up to set email alerts
|

Human Aldehyde Dehydrogenase Catalytic Activity and Structural Interactions with Coenzyme Analogs

Abstract: K(m) and V(max) values for 10 coenzyme analogs never previously studied with any aldehyde dehydrogenase and NADP(+) were compared with those for NAD(+) for three human aldehyde dehydrogenases (EC 1.2.1.3); the cytoplasmic E1 (the product of the aldh1 gene), the mitochondrial E2 (the product of the aldh2 gene) and the cytoplasmic E3 (the product of the aldh9 gene) isozymes. Structural information on changes in coenzyme-protein interactions were obtained via molecular dynamics (MD) studies with the E2 isozyme an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…A previous study indicated that ALDH1 had the broadest substrate specificity among isozymes of the ALDH enzyme family, and some residues of the active site were closely related with coenzyme binding, hydrophobicity, and structural perturbation [25]. Other mammalian-originated crystal structures of ALDH1 revealed that elephant ALDH1 has a Fig.…”
Section: Discussionmentioning
confidence: 97%
“…A previous study indicated that ALDH1 had the broadest substrate specificity among isozymes of the ALDH enzyme family, and some residues of the active site were closely related with coenzyme binding, hydrophobicity, and structural perturbation [25]. Other mammalian-originated crystal structures of ALDH1 revealed that elephant ALDH1 has a Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Within the ALDH family, research interest has been drawn to protein-ligand binding affinities and catalytic mechanisms 16 , 22 , 23 , 26 , 27 . The highly conserved sequence in the catalytic pocket defines similar residues for catalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, the thioester is hydrolysed by a water molecule to carboxylic acid. The sequential dissociation of carboxylic acid and NADH, which is the rate-limiting step, ends the reaction [14] , [16] .…”
Section: Introductionmentioning
confidence: 99%